Radical orchiectomy with iliohypogastric nerve blockage: A case report - Guldeniz Argun; Seher Altinel (Archives of Clinical and Experimental Surgery, 2017)
Iliohypogastric nerve blockage is rarely used for surgical operations in inguinal regions for the purpose of anesthesia without general or spinal anesthesia. A 33-year-old man with severe congenital chest and back deformities as well as cardiac and respiratory system problems had a testicular mass. General or spinal anesthesia may cause severe complications because of existing anatomical conditions and co-morbidities. Therefore, Iliohypogastric nerve blockage was performed with the aim of achieving anesthetic activity without general and spinal anesthesia. There were no side effects related to iliohypogastric nerve blockage during the postoperative period, including nausea, vomiting, hypotension, urinary retention, femoral nerve palsy, and local hematoma. Both the surgeon and the patients satisfaction were evaluated. Using iliohypogastric nerve blockage should be keep in mind for patients with anatomic or heart and pulmonary function problems with the goal of achieving anesthetic activity without general and spinal anesthesia. [Arch Clin Exp Surg 2017; 6(4.000): 214-216]